2015
DOI: 10.1039/c5ra18561k
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial surface display of metal binding peptides as whole-cell biocatalysts for 4-nitroaniline reduction

Abstract: Using recombinant microorganisms expressing metal binding peptides as whole-cell biocatalysts for 4-nitroaniline reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…The functions of FhuA, OmpA, Lpp-OmpA and IgA on the cell surface display of C. necator were compared, and quantitative research demonstrated that IgA was a more effective anchor protein than others. (Tsai et al 2015 ). Thus, IgA protease autotransporter was used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The functions of FhuA, OmpA, Lpp-OmpA and IgA on the cell surface display of C. necator were compared, and quantitative research demonstrated that IgA was a more effective anchor protein than others. (Tsai et al 2015 ). Thus, IgA protease autotransporter was used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…FhuA, OmpA, Lpp-OmpA and IgA were compared to function in cell surface display of C. necator, and quantitative research demonstrated that IgA was a more effective anchor protein than other. (Tsai et al 2015). Thus, IgA protease autotransporter was used in this study.…”
Section: Selection Of Surface Displayed Enzymesmentioning
confidence: 99%